Proceedings of the 5th International Conference on Computational Methods in Structural Dynamics and Earthquake Engineering (COM 2015
DOI: 10.7712/120115.3549.712
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Vertical Human-Structure Interaction for Footbridges

Abstract: Abstract.To allow for a more accurate description of crowd-induced loading, the present study aims to provide the necessary insights into vertical human-structure interaction (HSI) phenomena, to date ignored in current load models. A parametric study is performed to investigate the effects of the mechanical interaction between pedestrians, represented by simple lumped parameter models, and the supporting footbridge. The most significant HSI-effect for the lowfrequency modes of a footbridge, is in the effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Several studies have shown that pedestrians provide negligible additional damping to structures subjected to vertical vibration [14][15][16][17]. erefore, to depict the dynamic behaviour of the human body, some researchers have equated pedestrians to SMD system, which accounts for the effects of human mass, stiffness, and damping on the structure [18][19][20][21][22]. e moving SMD, introduced by Archbold [18], is applied into the HSI area and the SMD model has a better predictability in vibration response as compared to the MF model [20].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that pedestrians provide negligible additional damping to structures subjected to vertical vibration [14][15][16][17]. erefore, to depict the dynamic behaviour of the human body, some researchers have equated pedestrians to SMD system, which accounts for the effects of human mass, stiffness, and damping on the structure [18][19][20][21][22]. e moving SMD, introduced by Archbold [18], is applied into the HSI area and the SMD model has a better predictability in vibration response as compared to the MF model [20].…”
Section: Introductionmentioning
confidence: 99%